2021
DOI: 10.3390/ma14123305
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Edible Films Enhanced with Pomegranate Peel Extract: Study on Physical, Biological, Thermal, and Barrier Properties

Abstract: In the present study, pomegranate peel extract was used as a reinforcing agent in developing chitosan-based edible film. Different concentrations (0.2 g/mL, 0.4 g/mL, 0.6 g/mL, 0.8 g/mL, and 1.0 g/mL) of pomegranate peel extract were incorporated in chitosan-based edible film. A neat chitosan film was used as a control. This work covers the effect of pomegranate peel extract on the physical, biological, mechanical, thermal, and barrier properties of enriched chitosan-based edible film. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 95 publications
2
16
0
Order By: Relevance
“…Furthermore, lower transparency was noted for films with the highest addition of propolis extract. A similar observation was also made by Kumar et al [ 68 ], who found that the transparency of chitosan film was strongly dependent on the concentration of pomegranate peel extract in film. The changes in the transparency are due to incorporation of plant extracts, which are a natural source of colorants, into the film matrix [ 69 ].…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, lower transparency was noted for films with the highest addition of propolis extract. A similar observation was also made by Kumar et al [ 68 ], who found that the transparency of chitosan film was strongly dependent on the concentration of pomegranate peel extract in film. The changes in the transparency are due to incorporation of plant extracts, which are a natural source of colorants, into the film matrix [ 69 ].…”
Section: Resultssupporting
confidence: 85%
“…ME and GA in the film were significantly influenced (P < 0.05) WVP. Similarly, Kumar et al noticed a similar downward trend in the WVP when pomegranate peel extract was mixed into the chitosan film [14]. A decrease in the WVP may be closely associated with twisted paths formed in the film matrix with ME and GA, leading to a reduction in the WVP [15].…”
Section: Water Vapor Permeabilitymentioning
confidence: 77%
“…The main problem with cucumber preservations is water loss and condensation due to the high moisture content 22 . The extreme humidity atmosphere changes, air movement, dust on the sensor surfaces, and thermal radiation should be controlled to avoid disease developments, CO 2 injury, and hypoxia fermentation which leads to tissue damage, warts, microbial spoilage, and influence food safety 6 , 27 . Mir and Beaudry 28 , reported that higher CO 2 levels (5–10%) can cause yellowness and decay.…”
Section: Discussionmentioning
confidence: 99%